The Effectiveness of Music Therapy on Reducing Anxiety Levels in Maternity Mothers - Pinda Rasdiani; Omega DR Tahun (Global Health Science Group, 2023)
Anemia is one of the indirect causes of death of pregnant women. The prevalence of anemia of pregnant women in developing countries is between 35-75%. One of the causes of the high prevalence of anemia in pregnant women is the need for iron and must consume iron. However, this method is often disliked because it causes nausea and vomiting caused by the smell of iron. Therefore, a healthy and safe breakthrough is needed through non-pharmacological therapy, one of which is by consuming beets. The aimed of this research to analyze the effectiveness of beet consumption in overcoming anemia in 2nd trimester pregnancy in Lebak village in 2023. Research design was quasy experimental one group pre-post test. Researchers will give beet juice with beet juice as much as 100 grams consumed in the form of fruit juice / juice up to a volume of 250 ml / day for 14 days. The study was conducted in April 2023 on 30 second trimester pregnant women. Measurements were carried out using the sahli method. The statistical analysis used is an independent t test. Giving beet juice can increase hemoglobin levels of pregnant women so that there is a change in the diagnosis of pregnant women from moderate anemia to mild anemia. The results of the analysis showed this relationship was significant (p value 0.005 < 0.05).